2017
DOI: 10.1186/s12872-016-0445-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diabetes mellitus on long-term outcomes after repeat drug-eluting stent implantation for in-stent restenosis

Abstract: BackgroundWhether diabetes mellitus (DM) is a predictor of long-term adverse clinical outcomes after repeat drug eluting stent (DES) implantation for DES in-stent restenosis (ISR) remains controversial. We sought to evaluate the effect of DM on the long-term clinical outcomes in patients undergoing repeat DES implantation for DES-ISR lesions.MethodsIn the present study, 254 patients with DES-ISR were divided into DM or non-DM groups according to the presence or absence of DM. All patients received repeat 2nd g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
2
11
0
1
Order By: Relevance
“…Previous stent type, stent number, bifurcation lesion, ISR type, and repeat first-generation DES implantation were suggested as risk predictors of poor prognosis [ 36 – 39 ]. Conventional demographic risk factors, such as diabetes mellitus, failed to reach clinical significance after repeat PCI for ISR [ 40 ]. These findings suggested that the pathologic mechanisms of recurrent ISR are rather different from those of de novo coronary atherosclerosis, and implied that lesional, technical, and mechanical factors might play important roles in recurrent ISR development after repeat PCI for ISR.…”
Section: Discussionmentioning
confidence: 99%
“…Previous stent type, stent number, bifurcation lesion, ISR type, and repeat first-generation DES implantation were suggested as risk predictors of poor prognosis [ 36 – 39 ]. Conventional demographic risk factors, such as diabetes mellitus, failed to reach clinical significance after repeat PCI for ISR [ 40 ]. These findings suggested that the pathologic mechanisms of recurrent ISR are rather different from those of de novo coronary atherosclerosis, and implied that lesional, technical, and mechanical factors might play important roles in recurrent ISR development after repeat PCI for ISR.…”
Section: Discussionmentioning
confidence: 99%
“…Various clinical indexes including precipitating factors (eg, smoking and inflammation), biochemical parameters (eg, lipoprotein and cholesterol), coronary angiograms (eg, lesion size and number), or diseases history (eg, obesity, diabetes mellitus (DM), and hypertension) have been widely used for forecasting disease risk, monitoring disease severity, and predicting prognosis in CAD patients . However, limited information is available about the function of these clinical indexes on the risk of RASP and restenosis in CAD patients after PCI with drug‐eluting stents implantation.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are different conclusions to the research (L. Zhao et al, 2017) The same is the case with research results (Wan et al, 2016)diabetes mellitus is an unfavorable factor for restenosis. However, there was no significant difference between the restenosis group and the nonrestenosis group on the DM factor.…”
Section: Discussionmentioning
confidence: 94%